On the policy improvement algorithm for ergodic risk-sensitive control. Issue 4 (August 2021) - Arapostathis, Ari; Biswas, Anup; Pradhan, Somnath
Abstract : In this article we consider the ergodic risk-sensitive control problem for a large class of multidimensional controlled diffusions on the whole space. We study the minimization and maximization problems under either a blanket stability hypothesis, or a near-monotone assumption on the running cost. We establish the convergence of the policy improvement algorithm for these models. We also present a more general result concerning the region of attraction of the equilibrium of the algorithm.